Implementasi Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan Studi Penertiban Lalu Lintas di Wilayah Hukum Kepolisian Kota Deli Serdang - Muhammad Fadli Antony; Syahrul Bakti Harahap (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Traffic and road transportation have an important role in supporting national development and integration as part of efforts to advance general welfare as mandated by the 1945 Constitution of the Republic of Indonesia. The type of research used in this research is empirical juridical research, namely legal research. which is carried out by direct research or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data collection methods are techniques or methods that can be used by researchers to collect data. The data analysis technique used in this legal research uses qualitative analysis. Based on research that has been carried out, the duties and authority of the Deli Serdang City Traffic Police are fully in accordance with the provisions of Law Number 22 of 2009 concerning Road Traffic and Transportation by ordering and supervising the flow of traffic so that the safety and smoothness of traffic on public roads is maintained. . Various methods and forms of control are carried out by the police, but there are still traffic violators who violate traffic rules. In accordance with Law No. 22 of 2009 concerning Traffic and Road Transport Rules, and Standard Operating Procedures (SOP) owned by the Deli Serdang Regency Police Traffic Unit, control is carried out by warning and ticketing vehicles so that a ticket is given. Based on the results of the interviews, researchers could find out that the implementation of legal socialization carried out by law enforcers was not effective because they only socialized it at the school level and in the fields under Deli Serdang, but the people in the villages or sub-districts did not receive this socialization. Based on the results of the research, it is concluded that the obstacles that arise in the implementation of Law Number 22 of 2009 concerning Road Traffic and Transportation (Study of Traffic Control in the Legal Area of ​​the Deli Serdang City Police. There are several inhibiting factors that cause the implementation of Law No. 22. 2009 Article 77 Paragraph 1 concerning Traffic and Road Transport Rules for Riding Motorbikes in Deli Serdang Regency and to determine the effectiveness or ineffectiveness of legal regulations regarding the obligation to have a driver's license for driving motorized vehicles when driving in the LLAJ Law